Mechanical, technical, and biological complications of dental implants - Bukhari, Meisan Ali; Almalki, Nada Ghurmallah; Alkhudhayr, Abdullah Mohammed; Alburaiki, Sana Zaki; Aljumaiah, Alya Zyad; Haddad, Sawaher Khaleel; Jan, Heba Tariq; Alrowaithy, Hamad Murayshid; Alqahtani, Norah Ali; Toras, Mohanned Majdi; Alwadei, Rayan Hussain (International Journal Of Community Medicine And Public Health, 2021)
Evidence indicates the effectiveness of these modalities in enhancing the quality of life for the affected patients. Furthermore, many previous investigations have assessed the survival rates of these modalities. Estimates show that implant-supported fixed partial dentures have survival rates of up to 10 years. However, it should be noted that many complications were reported following implantation procedures. These events can reduce the prognosis of the process and worsen the outcomes by decreasing the survival rate. The present literature review aims to provide evidence regarding dental implants’ technical, biological, and mechanical complications. It should be noted that the incidence of these complications is generally decreasing based on the recent advance in the field. Adequate knowledge of the landmarks, careful treatment planning, proper case selection, obtaining a comprehensive history and information about implant procedure, and proper sterilization protocol are all different factors that can enhance the prognosis of the implant procedure. These can also reduce the frequency of the reported complications. Furthermore, these complications can be further reduced by being up to date with the recent advances and potential problem-solving research that usually provides adequate solutions that can reduce the frequency of these complications.